Panic bank runs - Hubert János Kiss; Ismael Rodriguez-Lara; Alfonso Rosa-Garcia (Hungarian Academy of Sciences, Institute of Economics, 2017)
We provide experimental evidence that panic bank runs occur in the absence of problems with fundamentals and coordination failures among depositors, the two main culprits identified in the literature. Depositors withdraw when they observe that others do so, even when theoretically they should not. Our findings suggest that panic also manifests itself in the beliefs of depositors, who overestimate the probability that a bank run is underway. Loss-aversion has a predictive power on panic behavior, while risk or ambiguity aversion do not.
Keywords: C7; C9; D8; G2; 330; bank runs; beliefs; panic; coordination; observability; loss aversion